Fleer, M., González Rey, F., and Jones, P. E. (eds.). (2020). Cultural Historical and Critical Psychology: Common Ground, Divergences, and Future Pathways. (28th April 2023) - Fernández, Loretta; Christensen, Joseph
Abstract : Fleer, M., González Rey, F., and Jones, P. E. (eds.). (2020). Cultural Historical and Critical Psychology: Common Ground, Divergences, and Future Pathways. Springer Nature Singapore Pte Ltd. 191 pp. $169.99 (Hard Cover) ISBN: 978-981-15-2208-6; $169.99 (Soft Cover) ISBN: 978-981-15-2211-6